Skill formation, cultural policies, and institutional hybridity: Bridging the gap between politics and policies at federal and state levels in Brazil - Netto, José Veríssimo Romão (Cogent social sciences, 2017)
This article analyses ideas, institutions and policy designs that aim at facilitating the resolution of social, economic and cultural problems through the direct involvement of civil society organizations, and other parties. More specifically, it focuses on two hybrid designs of partnerships in Brazil for the deliverance of public policies: the first sealed between the Brazilian government and paulista industrialists; the second, between the state of São Paulo government and civil society organizations. From the former stems a set of non-state autonomous entities that, among other functions, provide apprenticeship; from the latter, Social Organizations (OS) are contracted (contratualizadas) to deliver policies of culture. This study concludes that distinct ideas that opened windows of opportunity to design and implement hybrid partnerships for the deliverance of public policies beyond the state led to similar strategies of institutional insulation. The article finishes discussing possible implications of insulation to the Brazilian democracy to suggest some questions to lead to a new research agenda.